Optimizing the Extraction of Phenolic Compounds from Pistachio Hulls - Najmeh Pakdaman (Islamic Azad University, 2021)
Pistachio hull, as the dominant component of pistachio processing wastes, is a source of phenolics with antioxidant properties. Extracting these compounds from pistachio wastes has recently attracted a lot of attention. The current study aimed to identify the optimal conditions for extracting phenolics from pistachio hulls. Firstly, some parameters such as different sample to solvent ratios (1:10, 1:20, and 1:40), extraction temperatures (25, 45, and 65°C), and duration times (1, 2, and 3 h) were evaluated under extracting solvent of water. The content of total phenolics and antioxidant activity were determined using spectrophotometric methods. The results indicated that the highest phenolics (~35 mg g-1) were extracted at 2 h extraction time, 65 °C, and the sample to solvent ratio of 1:10 (optimum condition by the solvent of water). Secondly, other organic solvents of ethanol, methanol, and acetone 50% were evaluated to identify the best solvent under optimal conditions. All of these organic solvents were more efficient than water in extracting total phenolics (with antioxidant property) from pistachio hulls. However, the highest amount of total phenolics (~47 mg g-1) was extracted by ethanol. Optimizing the extraction of phenolic compounds from pistachio hulls would be important in terms of reducing human and environmental risks caused by the waste accumulation, as well as producing naturally beneficial compounds and using them instead of synthetic antioxidants in the human diet.